Executive Characteristics, Thin Capitalization, and Tax Avoidance after the Pandemic: Implications for SDG 16 - Anisa Hardianingrum; Eko Arief Sudaryono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine the effect of thin capitalization on tax avoidance and investigates whether executive characteristics moderate this relationship in multinational companies after the COVID-19 pandemic. The study is motivated by concerns regarding tax avoidance practices and the need to strengthen corporate tax compliance in support of Sustainable Development Goal 16, which promotes effective, accountable, and transparent institutions. Method: Employing a quantitative approach using secondary data obtained from annual reports and financial statements of multinational consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during 2021–2022. Using purposive sampling, 41 companies were selected, resulting in 82 firm-year observations. The hypotheses were tested using panel data regression and moderated regression analysis (MRA). Results: The findings indicate that thin capitalization significantly affects tax avoidance. The relationship is negative, suggesting that companies tend to utilize debt financing within regulatory limits rather than aggressively using debt to reduce tax obligations. Furthermore, executive characteristics, proxied by corporate risk, significantly moderate the relationship between thin capitalization and tax avoidance by weakening its effect. This finding suggests that executives tend to exercise caution in implementing debt-based tax strategies after the pandemic. Novelty: Extending the tax accounting literature by demonstrating the moderating role of executive characteristics in the relationship between thin capitalization and tax avoidance in the post-pandemic period. The findings also provide empirical evidence supporting the Theory of Reasoned Action (TRA) and offer policy insights regarding the implementation of interest expense-to-EBITDA limitations to strengthen tax compliance and support SDG 16.